Cu-Mxene two-dimensional nanosheet materials, their preparation methods and applications
By using Cu-Mxene two-dimensional nanosheet material as an electrocatalyst, the problem of low selectivity when electrocatalytic coupling N2 and CO2 is urea is solved, and higher C-N coupling selectivity and Faraday efficiency are achieved, which is suitable for large-scale production applications.
Patent Information
- Application Number
- CN202210927052.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-08-03
AI Technical Summary
The prior art has low selectivity when electrocatalytic coupling of N2 and CO2 as urea, and it is difficult to activate inert N2 and CO2 molecules, and there is competition between hydrogen evolution reaction and non-coupled electrochemical reduction reaction.
The Cu-Mxene two-dimensional nanosheet material was used as an electrocatalyst to synthesize Mxene through HF etching, and atomic deposition Cu source was uniformly loaded on the Mxene nanosheet to form an accordion-shaped Cu-Mxene two-dimensional nanosheet material.
It improves the adsorption amount and reduction catalytic properties of nitric acid and CO2, enhances the selectivity of C-N coupling, improves Faraday efficiency, and is suitable for large-scale production applications.
Smart Images

Figure CN115181989B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a preparation method of a Cu-Mxene two-dimensional nanosheet material and an application of the Cu-Mxene material as an electrocatalyst in CN coupling to urea. Background Art
[0002] Urea is the first organic compound produced from inorganic raw materials. Due to its high nitrogen content (46%) and its easy conversion to ammonia (NH3) in soil, urea is now the most commonly used nitrogen fertilizer in the world. Urea is produced in greater quantities by mass than any other organic chemical. Although more than 90% of urea produced is used as fertilizer, it also has important applications in other areas. Electrocatalytic coupling of N2 and CO2 can achieve urea synthesis under normal temperature and pressure conditions, but the selectivity of the process is low. This is mainly limited by: (1) the difficulty in activating inert N2 and CO2 molecules on the catalyst surface; (2) competition with the hydrogen evolution reaction (HER); and (3) competition between selective CN coupling and uncoupled electrochemical reduction reactions. A feasible alternative is to use the N=O bond dissociation energy (204 kJ·mol -1 ) much lower nitrate (NO3 - ) replaces N2 (N≡N bond dissociation energy: 941 kJ·mol -1 ) is coupled with CO2 to electrocatalyze the synthesis of urea. However, this route requires finding a suitable catalyst to achieve selective CN coupling to enhance urea selectivity and simultaneously suppress HER competing reactions to improve Faradaic efficiency (FE).
[0003] Therefore, in order to develop the emerging electrochemical urea synthesis, it is highly desirable to be able to convert NO3 - Cheap and efficient electrocatalysts that are fixed to CO2. In the past decade, the application of two-dimensional (2D) materials in the field of electrocatalysis has attracted much attention due to their large specific surface area and more exposed active sites. Recent theoretical studies have shown that MXene can provide good activity and selectivity for CO2RR. Cu is also mentioned in many reports to be beneficial to CO2RR. MXene materials refer to two-dimensional layered materials derived from transition metal carbon / nitrogen / carbonitrides (such as Ti3C2), specifically a class of material systems composed of Mn+1XnTx elements (where M represents an early transition metal element, X represents C or N, T refers to the group / modification on the surface of the two-dimensional material, and n usually ranges from 1 to 3). Summary of the invention
[0004] One object of the present invention is to provide a method for preparing Cu-Mxene two-dimensional nanosheet electrocatalyst.
[0005] The Cu-Mxene two-dimensional nanosheet electrocatalyst of the present invention is composited by Ti3AlC2, hydrofluoric acid, concentrated hydrochloric acid and ALD copper source, and the specific method is as follows:
[0006] Step (1) adding a mixture of hydrofluoric acid having a mass concentration of 40 to 50% and concentrated hydrochloric acid having a concentration of 12 mol / L in a volume ratio of 0.8 to 1.2:1 into a reaction vessel;
[0007] Step (2) adding Ti3AlC2 powder to the mixed solution and stirring by magnetic force to form a suspension; adding 50-100 g Ti3AlC2 powder per liter of the mixed solution;
[0008] Step (3) placing the suspension in a constant temperature oil bath and reacting at 40-50° C. for 45-50 hours;
[0009] Step (4) After the reaction is completed, the temperature is lowered to room temperature, and the reaction product is centrifuged and washed with deionized water for multiple times until the pH value of the washing solution reaches between 6.9 and 7.1; the centrifugal washing speed is 3000-5000 r / min;
[0010] Step (5) vacuum drying at 50-80° C. for 12-36 hours to obtain the Mxene material;
[0011] Step (6) placing the Mxene material in an atomic deposition device, depositing an ALD copper source, with an N2 pulse time of 100 to 200 seconds, and depositing 5 to 15 layers of the ALD copper source to obtain a Cu-Mxene two-dimensional nanosheet material.
[0012] The second object of the present invention is to provide a Cu-Mxene two-dimensional nanosheet material prepared by the above method.
[0013] The third object of the present invention is to provide the application of the Cu-Mxene two-dimensional nanosheet material as an electrocatalyst in the coupling of CN to urea.
[0014] Synergistic active sites composed of atomically deposited transition metal sources are proposed as an effective way to improve the performance of nitric acid and carbon dioxide reduction catalysts. Here, we report the synthesis of MXene by simple HF etching and atomically deposited Cu source to uniformly load it on MXene nanosheets (accordion-shaped). This tunability can improve the adsorption of nitrate in nitric acid reduction and CO2 adsorption at the same time. In recent years, MXene has become an important candidate for catalytic water splitting due to its unique physical and electronic properties. High hydrophilicity and solution processability make MXene stable and durable in acidic, alkaline and seawater. High electronic conductivity enables MXene to promote efficient electronic charge transport at the electrode-electrolyte interface as a large-area conductive 2D substrate when combined with other highly active but less conductive co-catalysts. The combination of these properties overcomes the limitations of conventional carbon-based supports, such as graphene, whose hydrophobicity restricts its application in water electrocatalysis. Hybridization also generates additional catalytically active motifs at the interface and modulates the electronic structure to enhance intrinsic catalytic activity. Given that the Fermi energy (EF) position of MXene is similar to that of H + / H2 reduction potentials are closely matched, and efficient H + adsorption, and the excellent electrocatalytic water splitting performance as mentioned above. In addition, at room temperature or in an electrolyte environment, the basal surface of MXene has T x These T x The groups usually contain electronegative elements (fluorine, oxygen, chlorine), which can change the effective work function of the MXene and produce unique interactions between the MXene and the intermediate molecular adsorbate. In the CO2 reduction reaction, these unusual interactions provide thermodynamic and kinetic pathways to achieve reactions that were previously impossible on transition metal catalysts.
[0015] The overall morphology of the Cu-Mxene two-dimensional nanosheet material of the present invention is accordion-shaped, due to the nanolayer structure and the presence of Tx groups on the basal surface of MXene. These Tx groups usually contain electronegative elements (fluorine, oxygen, chlorine), which can change the effective work function of MXene and produce unique interactions between MXene and intermediate molecular adsorbates. In the CO2 reduction reaction, these unusual interactions provide thermodynamic and kinetic pathways, which can achieve reactions that could not be performed on transition metal catalysts. It is made to produce higher electrocatalytic activity in the electrochemical workstation and has broad application prospects in the field of electrocatalysis. Moreover, the synthesis method provided by the present invention has the characteristics of simple process, low energy consumption, mild conditions and good product morphology, and is suitable for large-scale production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1This is a schematic diagram of TEM test results of a Cu-Mxene two-dimensional nanosheet material prepared in one embodiment of the present invention;
[0017] Figure 2 This is a schematic diagram of XRD test results of a Cu-Mxene two-dimensional nanosheet material prepared in one embodiment of the present invention;
[0018] Figure 3 Schematic diagram of the activity and Faraday efficiency of the embodiments of the present invention and the comparative examples at -0.6V;
[0019] Figure 4 Schematic diagram of the activity and Faraday efficiency of an embodiment of the present invention at different voltages. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with specific embodiments and drawings. It should be understood that these embodiments are only used to illustrate the present invention but not to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
[0021] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0022] The raw materials used in the present invention have no particular restrictions on their purity, and analytically pure materials are preferably used. The equipment used in the present invention has no particular restrictions, and commonly used devices that can meet the technical solutions of the present invention are used.
[0023] Example 1
[0024] Step (1) 1.2 L of hydrofluoric acid with a mass concentration of 40% and 1 L of concentrated hydrochloric acid with a concentration of 12 mol / L are mixed and added into a reaction container;
[0025] Step (2) adding 160 g Ti3AlC2 powder and stirring by magnetic force to form a suspension;
[0026] Step (3) placing the suspension in a constant temperature oil bath and reacting at 42° C. for 48 hours;
[0027] Step (4) After the reaction is completed, the temperature is lowered to room temperature, and the reaction product is washed by centrifugation several times with deionized water (at a speed of 5000 r / min) until the pH value of the washing liquid reaches between 6.9 and 7.1;
[0028] Step (5) vacuum drying at 50° C. for 36 hours to obtain the Mxene material;
[0029] Step (6) placing the Mxene material in an atomic deposition device, depositing an ALD copper source, with an N2 pulse time of 120 s and a number of deposited ALD copper source layers of 5 to obtain a Cu-Mxene two-dimensional nanosheet material.
[0030] Example 2
[0031] Step (1) 1L of hydrofluoric acid with a mass concentration of 45% and 1L of concentrated hydrochloric acid with a concentration of 12 mol / L are mixed and added into a reaction container;
[0032] Step (2) adding 100 g Ti3AlC2 powder and stirring by magnetic force to form a suspension;
[0033] Step (3) placing the suspension in a constant temperature oil bath and reacting at 40° C. for 50 hours;
[0034] Step (4) After the reaction is completed, the temperature is lowered to room temperature, and the reaction product is washed by centrifugation several times with deionized water (at a speed of 3000 r / min) until the pH value of the washing liquid reaches between 6.9 and 7.1;
[0035] Step (5) vacuum drying at 60° C. for 30 hours to obtain the Mxene material;
[0036] Step (6) placing the Mxene material in an atomic deposition device, depositing an ALD copper source, with an N2 pulse time of 100 s and 8 layers of deposited ALD copper source to obtain a Cu-Mxene two-dimensional nanosheet material.
[0037] Example 3
[0038] Step (1) 0.8 L of 50% hydrofluoric acid and 1 L of 12 mol / L concentrated hydrochloric acid were mixed and added into a reaction container;
[0039] Step (2) adding 120 g Ti3AlC2 powder and stirring by magnetic force to form a suspension;
[0040] Step (3) placing the suspension in a constant temperature oil bath and reacting at 45° C. for 48 hours;
[0041] Step (4) After the reaction is completed, the temperature is lowered to room temperature, and the reaction product is washed by centrifugation several times with deionized water (at a speed of 4000 r / min) until the pH value of the washing liquid reaches between 6.9 and 7.1;
[0042] Step (5) vacuum drying at 70° C. for 18 hours to obtain the Mxene material;
[0043] Step (6) placing the Mxene material in an atomic deposition device, depositing an ALD copper source, with an N2 pulse time of 150 s and 15 layers of deposited ALD copper source to obtain a Cu-Mxene two-dimensional nanosheet material.
[0044] Example 4
[0045] Step (1) 0.9 L of hydrofluoric acid with a mass concentration of 48% and 1.1 L of concentrated hydrochloric acid with a concentration of 12 mol / L were mixed and added into a reaction container;
[0046] Step (2) adding 200 g Ti3AlC2 powder and stirring by magnetic force to form a suspension;
[0047] Step (3) placing the suspension in a constant temperature oil bath and reacting at 50° C. for 45 hours;
[0048] Step (4) After the reaction is completed, the temperature is lowered to room temperature, and the reaction product is washed by centrifugation several times with deionized water (at a speed of 4200 r / min) until the pH value of the washing solution reaches between 6.9 and 7.1;
[0049] Step (5) vacuum drying at 80° C. for 12 hours to obtain the Mxene material;
[0050] Step (6) placing the Mxene material in an atomic deposition device, depositing an ALD copper source, with an N2 pulse time of 200 s and 12 layers of deposited ALD copper source to obtain a Cu-Mxene two-dimensional nanosheet material.
[0051] Example 5. Deposition of 5 layers of copper source:
[0052] Put 12ml of 49% HF solution and 12mL of 12mol / L HCl into a polytetrafluoroethylene beaker, weigh 1.8g of Ti3AlC2 powder sample and slowly put it into the mixed solution containing HF solution and HCl, add a magnetic stirrer, put it on the magnetic stirrer, and then tighten the lid of the same material. The above suspension was placed in a constant temperature oil bath, maintained at 45°C, and reacted continuously for 48 hours. After the reaction was completed, it was cooled to room temperature, and the mixture was carefully transferred into a centrifuge tube in a fume hood, and then the mixture was washed with deionized water and centrifuged several times at high speed (4000rpm) until the pH value was about 7. Finally, the sample was stored in a vacuum oven (60 degrees Celsius) and left for 24 hours. The prepared Mxene sample was deposited with 5 layers of copper source in atomic deposition. The final product was made into a catalyst solution, and an appropriate amount was dropped on a 1cm×1cm carbon paper to measure its reduction activity.
[0053] Weigh 4 mg of the final product, add 750u of deionized water, 200u of isopropanol and 50u of naphthol to make a catalyst solution, take 30u and drop it on 1cm×1cm carbon paper, and measure its reduction activity in the electrolyte 0.1M KNO3+0.1M KHCO3 with continuous CO2 flow.
[0054] Example 6. Deposition of 10 layers of copper source:
[0055] Put 12ml of 49% HF solution and 12mL of 12mol / L HCl into a polytetrafluoroethylene beaker, weigh 1.8g of Ti3AlC2 powder sample and slowly put it into the mixed solution containing HF solution and HCl, add a magnetic stirrer, put it on the magnetic stirrer, and then tighten the lid of the same material. The above suspension was placed in a constant temperature oil bath, maintained at 45°C, and reacted continuously for 48 hours. After the reaction was completed, it was cooled to room temperature, and the mixture was carefully transferred into a centrifuge tube in a fume hood, and then the mixture was washed with deionized water and centrifuged several times at high speed (4000rpm) until the pH value was about 7. Finally, the sample was stored in a vacuum oven (60 degrees Celsius) and left for 24 hours. The prepared Mxene sample was deposited with 10 layers of copper source in atomic deposition. The final product was made into a catalyst solution, and an appropriate amount was dropped on a 1cm×1cm carbon paper to measure its reduction activity.
[0056] Weigh 4 mg of the final product, add 750u of deionized water, 200u of isopropanol and 50u of naphthol to make a catalyst solution, take 30u and drop it on 1cm×1cm carbon paper, and measure its reduction activity in the electrolyte 0.1M KNO3+0.1M KHCO3 with continuous CO2 flow.
[0057] Example 7. Deposition of 15 layers of copper source:
[0058] Put 12ml of 49% HF solution and 12mL of 12mol / L HCl into a polytetrafluoroethylene beaker, weigh 1.8g of Ti3AlC2 powder sample and slowly put it into the mixed solution containing HF solution and HCl, add a magnetic stirrer, put it on the magnetic stirrer, and then tighten the lid of the same material. The above suspension was placed in a constant temperature oil bath, maintained at 45°C, and reacted continuously for 48 hours. After the reaction was completed, it was cooled to room temperature, and the mixture was carefully transferred into a centrifuge tube in a fume hood, and then the mixture was washed with deionized water and centrifuged several times at high speed (4000rpm) until the pH value was about 7. Finally, the sample was stored in a vacuum oven (60 degrees Celsius) and left for 24 hours. The prepared Mxene sample was deposited with 10 layers of copper source in atomic deposition. The final product was made into a catalyst solution, and an appropriate amount was dropped on a 1cm×1cm carbon paper to measure its reduction activity.
[0059] Weigh 4 mg of the final product, add 750u of deionized water, 200u of isopropanol and 50u of naphthol to make a catalyst solution, take 30u and drop it on 1cm×1cm carbon paper, and measure its reduction activity in the electrolyte 0.1M KNO3+0.1M KHCO3 with continuous CO2 flow.
[0060] Comparative Example 1. Deposition of 0 layer of copper source:
[0061] Put 12ml of 49% HF solution and 12mL of 12mol / L HCl into a polytetrafluoroethylene beaker, weigh 1.8g of Ti3AlC2 powder sample and slowly put it into the mixed solution containing HF solution and HCl, add a magnetic stirrer, put it on a magnetic stirrer, and then tighten the lid of the same material. The above suspension was placed in a constant temperature oil bath, maintained at 45°C, and reacted continuously for 48 hours. After the reaction was completed, it was cooled to room temperature, and the mixture was carefully transferred to a centrifuge tube in a fume hood, and then the mixture was washed with deionized water and centrifuged several times at high speed (4000rpm) until the pH value was about 7. Finally, the sample was stored in a vacuum oven (60 degrees Celsius) and left for 24 hours. The final product was made into a catalyst solution, and an appropriate amount was dropped on a 1cm×1cm carbon paper to measure its reduction activity.
[0062] Weigh 4 mg of the final product, add 750u of deionized water, 200u of isopropanol and 50u of naphthol to make a catalyst solution, take 30u and drop it on 1cm×1cm carbon paper, and measure its reduction activity in the electrolyte 0.1M KNO3+0.1M KHCO3 with continuous CO2 flow.
[0063] The prepared Cu-Mxene two-dimensional nanosheet material was tested for carbon dioxide nitric acid CN coupling catalytic activity, and the test method was as follows:
[0064] The test adopts a three-electrode system, with an electrode clamp holding carbon paper as the working electrode, a silver / silver chloride electrode as the reference electrode, and a platinum mesh as the counter electrode. A 0.1M KNO3+0.1M KHCO3 mixed electrolyte solution is used to measure the reduction activity under CO2. The applied voltage range is -0.1 to -1.0V, and the test duration is 2 hours.
[0065] Performance characterization: For Examples 5-7 of the present invention, the Cu-Mxene two-dimensional nanosheet materials prepared were subjected to SEM test to observe their morphology, XRD test, and carbon dioxide nitric acid CN coupling electrochemical test.
[0066] Performance characterization results:
[0067] 1. By Figure 1It can be seen that the Cu-Mxene two-dimensional nanosheet material prepared by the method of the present invention is in an accordion shape.
[0068] 2. By Figure 2 It can be seen that the XRD pattern of the Cu-Mxene two-dimensional nanosheet material prepared by the method of the present invention can well match the card in the literature.
[0069] 3. By Figure 3 It can be seen that the Cu-Mxene two-dimensional nanosheet material prepared by the method of the present invention has the highest urea synthesis activity and Faraday efficiency in the mixed electrolyte of 0.1 M KHCO3 and 0.1 M KNO3, and the Cu-Mxene two-dimensional nanosheet material prepared by Example 6.
[0070] 4. By Figure 4 It can be seen that in the mixed electrolyte of 0.1 M KHCO3 and 0.1 M KNO3, the Cu-Mxene two-dimensional nanosheet material prepared in Example 6 has urea synthesis activity and Faraday efficiency at different voltages.
Claims
1. A method for preparing Cu-Mxene two-dimensional nanosheet material, characterized in that: The method is as follows: Step (1) adding hydrofluoric acid having a mass concentration of 40-50% and concentrated hydrochloric acid having a concentration of 12 mol / L into a reaction container at a volume ratio of 0.8-1.2:1; Step (2) adding Ti3AlC2 powder to the mixed solution and stirring by magnetic force to form a suspension; adding 50-100 g Ti3AlC2 powder per liter of the mixed solution; Step (3) placing the suspension in a constant temperature oil bath and reacting at 40-50° C. for 45-50 hours; Step (4) After the reaction is completed, the temperature is lowered to room temperature, and the reaction product is washed with deionized water by centrifugation for multiple times until the pH value of the washing solution reaches between 6.9 and 7.1; Step (5) vacuum drying at 50-80° C. for 12-36 hours to obtain the Mxene material; Step (6) placing the Mxene material in an atomic deposition device, depositing an ALD copper source, with an N2 pulse time of 100 to 200 seconds, and depositing 5 to 15 layers of the ALD copper source to obtain a Cu-Mxene two-dimensional nanosheet material.
2. A Cu-Mxene two-dimensional nanosheet material prepared by the method of claim 1.
3. Use of a Cu-Mxene two-dimensional nanosheet material as claimed in claim 2 as an electrocatalyst in CN coupling to urea.